A 1, 470 nm diode laser in stapedotomy: Mechanical, thermal, and acoustic effects. Issue 6 (11th April 2017) - Koenraads, Simone P. C.; de Boorder, Tjeerd; Grolman, Wilko; Kamalski, Digna M. A.
Abstract : Background and Objectives: Multiple laser systems have been investigated for their use in stapes surgery in patients with otosclerosis. The diode 1, 470 nm laser used in this study is an attractive laser system because it is easily transported and relatively inexpensive in use. This wavelength has relative high absorption in water. This study aimed to investigate the mechanical, thermal, and acoustic effects of the diode 1, 470 nm laser on a stapes in an inner ear model. Materials and Methods: Experiments were performed in an inner ear model including fresh frozen human stapes. High‐speed imaging with frame rates up to 2, 000 frames per second (f/s) was used to visualize the effects in the vestibule during fenestration of the footplate. A special high‐speed color Schlieren technique was used to study thermal effects. The sound produced by perforation was recorded by a hydrophone. Single pulse settings of the diode 1, 470 nm laser were 100 ms, 3 W. Results: Diode 1, 470 nm laser fenestration showed mechanical effects with small vapor bubbles and pressure waves pushed into the vestibule. Thermal imaging visualized an increase temperature underneath the stapes footplate. Acoustic effects were limited, but larger sounds levels were reached when vaporization bubbles arise and explode in the vestibule. Conclusion: The diode 1, 470 nm laser highly absorbs in perilymph and is capable of forming a clear fenestration in the stapes. An overlapping laser pulse will increase the risk of vapor bubbles, pressure waves, and heating the vestibule. As long as we do not know the possible damage of these effects to the inner ear function, it seems advisable to use the laser with less potential harm. Lasers Surg. Med. 49:619–624, 2017. © 2017 Wiley Periodicals, Inc.